The Effect of Autogenic Relaxation on Blood Pressure in Hypertensive Patients - Anita Shinta Kusuma; Evin Kristiani (Sekolah Tinggi Ilmu Kesehatan Ngesti Waluyo, 2021)
Hypertension case is increasing from year to years. Based on World Health Organization (WHO) data in 2015 showed around 1.13 billion people in the world have hypertension, meaning 1 in 3 people in the world are diagnosed with hypertension. Hypertension is often referred to as a